A rare balanced parental t (21q; 21q) Robertsonian translocation that results in Down syndrome in all viable pregnancies - Vikraman, Seneesh Kumar; Chandra, Vipin; Balakrishanan, Bijoy; Batra, Meenu; Kuriakose, Rekha; Kannoly, Gopinathan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
We report a case of a rare balanced Robertsonian translocation, t (21q; 21q) in one of the parents that results in adverse pregnancy outcome in 100 % of cases, either first trimester miscarriages or Down syndrome in all viable fetuses. The case highlights the role of optimum genetic evaluation of all cases of reproductive disorders as they can have profound effect over prognosis and further management.